2022
DOI: 10.1016/j.amsu.2022.103305
|View full text |Cite
|
Sign up to set email alerts
|

Factors affecting medical student's decision in choosing a future career specialty: A cross-sectional study

Abstract: Background Diversity in the specialties is essential to provide optimal health care. Future career specialties chosen by the students had great significance for balanced doctor's distribution in different specialties, as it determines the composition of the physician workforce. Therefore, there has been a deeper interest in the issues of career preference among medical students. We aimed to determine and assess the factors perceived to be significantly attractive when choosing a future specialty. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(22 citation statements)
references
References 18 publications
1
11
0
Order By: Relevance
“…Moreover, from our first year of experience, we noticed that the ratio of inactive members to active ones was 1:5. 17 19 …”
Section: Discussionmentioning
confidence: 99%
“…Moreover, from our first year of experience, we noticed that the ratio of inactive members to active ones was 1:5. 17 19 …”
Section: Discussionmentioning
confidence: 99%
“…Likewise, it has been observed that students in medicine, nursing, and other healthcarerelated subjects often choose their jobs based on "job prospect," i.e., social prestige, financial incentives, and promotion prospects [16,57]. Sundly and Galway [13] observed that engineering students often select their careers based on social prestige or social value, while some medical students emphasize high payment over social prestige or job prospects [17], especially those involved in emergency medicine [15]. Regarding "job motive," previous studies on university students in Bangladesh showed that students' career choice was substantially influenced by inspiration from their instructors/teachers' as well as by the scope of spending quality time with family [4,11].…”
Section: Discussionmentioning
confidence: 99%
“…Work and subject experiences positively impact the choice of career [6]. For example, some medical students, especially men, are more interested in cardiothoracic surgery [15][16][17], while others, women, in particular, prefer primary care specialties and nursing [18,19]. In contrast, students from business studies backgrounds prefer private jobs to public/government jobs [11].…”
Section: Introductionmentioning
confidence: 99%
“…9 Motivators for a career in health care are humanitarian ideals, societal views (job opportunities, prestige, job security), medical background of family members and scientific reasons (curiosity in scientific and medical knowledge, academia, specific medical subspecialities). [10][11][12] Students' motivation is based on the pursuit of different levels of needs following the Maslow's hierarchy. 13 Levels of student's motivation has been investigated at different phases of medical education finding highest motivation scores in early semesters.…”
Section: Introductionmentioning
confidence: 99%